Circular RNA Expression Profiles in Nasopharyngeal Carcinoma by Sequence Analysis - Yang, Jing; Gong, Yongqian; Jiang, Qingshan; Liu, Lijun; Li, Shuyan; Zhou, Quanjun; Huang, Fang; Liu, Zhifeng (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs), as a burgeoning sort of non-coding RNAs (ncRNAs), can regulate the expression of parental genes as miRNA sponges. This study was designed to explore the circRNA expression profile of nasopharyngeal carcinoma (NPC). High-throughput sequencing was performed to identify the circRNA expression profile of NPC patients compared with healthy controls. A total of 93 upregulated circRNAs and 77 downregulated circRNAs were identified. The expression levels of the top three upregulated and three downregulated circRNAs annotated by circBase were validated by quantitative real-time PCR (qRT-PCR). GO and KEGG analyses showed that these differentially expressed circRNAs were potentially implicated in NPC pathogenesis. CircRNA-miRNA-target gene network analysis revealed a potential mechanism that hsa_circ_0002375 (circKITLG) may be involved in NPC through sponging up miR-3198 and interfering with its downstream targets. Silencing of circKITLG inhibited NPC cell proliferation, migration, and invasion in vitro. This study provides a leading and fundamental circRNA expression profile of NPC.